La realidad jurídica del trabajo informal en el derecho comparado latinoamericano. - Rea Alarcón, Jéssica Alexandra (2025)
The legal reality of informal work, in Ecuador and in most of the countries where this social problem is evident is similar, since little or no regulation of this informal sector, especially at the legal level, is serious since in the context and the reality in which these work activities are carried out in most cases are precarious, they do not comply with the minimum standards of guarantees for workers, thus violating their rights. Although in our country article 325 of the Constitution of the Republic of Ecuador indicates that “All work modalities are recognized, in relation to dependency or autonomous” (Constitution of the Republic of Ecuador, 2008, p. 161), guaranteeing With this, the development and execution of autonomous or informal works, it is no less true that there is only that pronouncement in this regard, since if the Labor Code is used there is no broader normative development on the subject, to this is added the This is a serious problem, especially for street vendors or merchants who suffer various impairments to their rights, many times under the application of ordinances that undermine the rights of self-employed workers. Mainly economic factors, situations of poverty, the change of labor for machinery, are the causes that have led to the reduction or even almost elimination of sources of formal work, which affects the growth of informal work which for a short time or Null legal regulation is a source of violations of workers' rights.